(untitled) (The International Journal for Scientific Research, 2026)
This study aims to measure the impact of utilizing artificial intelligence (AI) techniques in talent management on the efficiency of governmental health institutions in Saudi Arabia, focusing on three main dimensions of talent management: recruitment, development, and retention of talents. The study adopted a descriptive-analytical approach using a questionnaire consisting of two parts: demographic data and statements rated on a Likert scale to assess the effect of AI on talent management and institutional performance efficiency. The sample included 260 employees from governmental health institutions, covering various job categories (administrative staff, doctors, nurses, health technicians, and others). The results revealed that employing AI techniques has a positive and statistically significant impact on institutional efficiency, and all dimensions of talent management using AI significantly contribute to improving institutional performance. Accordingly, the study recommends increasing investment in AI applications for recruitment, development, and retention of talents, integrating these technologies into administrative and service processes, enhancing staff awareness and training, and conducting future studies to expand the applicability of the findings.